2015
DOI: 10.1002/cncr.29044
|View full text |Cite
|
Sign up to set email alerts
|

The RET oncogene in papillary thyroid carcinoma

Abstract: Papillary thyroid carcinoma (PTC) is the most common form of thyroid cancer, accounting for greater than 80% of cases. Surgical resection, with or without postoperative radioiodine therapy, remains the standard of care for patients with PTC, and the prognosis is generally excellent with appropriate treatment. Despite this, significant numbers of patients will not respond to maximal surgical and medical therapy and ultimately will die from the disease. This mortality reflects an incomplete understanding of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 69 publications
1
63
0
4
Order By: Relevance
“…Rearrangements of other RTKs have also been reported in minor subsets of IMT. The RET fusion gene is well known in papillary thyroid carcinoma . Antonescu et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rearrangements of other RTKs have also been reported in minor subsets of IMT. The RET fusion gene is well known in papillary thyroid carcinoma . Antonescu et al .…”
Section: Discussionmentioning
confidence: 99%
“…The RET fusion gene is well known in papillary thyroid carcinoma. 37 Antonescu et al reported the presence of RET rearrangement in only one of 62 IMTs, although no fusion partner gene has been discovered to date. 21 In the current study, we failed to find RET rearrangement by FISH, suggesting that such a rearrangement may be an extremely rare event in IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, 13 different RET/PTC oncogenes have been discovered, and RET/PTC1 and RET/PTC3 represent the most common types, accounting for approximately 90% of RET-associated PTC [51, 52]. Only one study compared the occurrence of RET/PTC between TCV and cPTC in literature.…”
Section: Bio-markersmentioning
confidence: 99%
“…RET binds the family of GDNF (glial neuron derived factor) neurotrophic growth factors. In normal conditions, binding of the ligand to the extracellular portion of the receptor allows dimerization of the receptor, phosphorylation in tyrosine kinase cytoplasmic domain and consequent activation of the MAPK signaling pathway (Prescott, 2015).…”
Section: Ret/ptc Rearrangements:-mentioning
confidence: 99%